Effect of curcumin supplement or placebo in delayed onset muscle soreness: a systematic review and meta-analysis - Natthanichar Rattanaseth; Patteera Panyarapeepat; Janisa Andrea Muljadi; Kornkit Chaijenkij; Jatupon Kongtharvonskul (Bulletin of the National Research Centre, 2021)
Abstract Background There are multiple strategies that have been suggested to attenuate delayed onset muscle soreness (DOMS). Curcumin has been shown to reduce exercise-induced oxidative stress (OS) and inflammation. However, currently, there is still controversy. Main body of the abstract We conduct this meta-analysis according to the PRISMA guidelines. Relevant studies were included from Medline and Scopus from the date of inception to May 04th, 2021 that reported VAS score, blood markers (creatinine kinese (CK), tumor necrotic factor (TNF)-α and interleukin (IL)-6) and range of motion of either group. There were total of 13 studies including 202 and 176 persons in curcumin and placebo group. The unstandardized mean difference (UMD) of VAS muscle soreness in post-exercise, 1, 2, 3 and 4 days was − 0.12 (95% CI − 0.46, 0.22), − 0.38 (− 0.83, 0.08), − 0.67 (− 1.19, − 0.16), − 0.86 (− 1.38, − 0.34), − 0.81 (− 1.27, − 036) and − 1.24 (− 1.50, − 0.99) scores lower in curcumin when compared to placebo. The UMD of CK was − 11.07 (95% CI − 24, 1.86), − 37.51 (− 68.04, − 6.97), − 45.40 (− 95.67, 4.86), − 53.33 (− 128.11, 21.45), − 90.98 (− 173.45, − 8.51) and 117.84 (− 338.69, 574.37) lower in curcumin when compared to placebo. No statistically significantly differences were noted for IL-6, TNF-α and ROM between two groups. Short conclusion This meta-analysis suggested that curcumin supplement reduced delayed onset muscle soreness and CK after exercise in 1, 2, 3, and 4 days when compared to placebo. However, TNF and IL were not affected by curcumin ingestion. Level of evidence I.